2019
DOI: 10.1080/13607863.2019.1695742
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial interventions for dementia in low- and middle-income countries (LMICs): a systematic review of effectiveness and implementation readiness

Abstract: Introduction: Despite wide uptake in high-income countries (HICs), less is known about the effectiveness and implementation of psychological, social and cognitive interventions in low-and middle-income countries (LMICs). Despite this, such interventions are increasingly used. The aim of this review was to appraise the effectiveness and implementation readiness of psychosocial interventions for people with dementia in LMICs. Methods: A systematic search of databases from 1998-2019. Studies were rated on two sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 60 publications
0
21
0
2
Order By: Relevance
“…Using an innovative methodology developed using the CFIR and extensive stakeholder engagement, five Implemention Plans for CST were produced for three countries. The systematic development of methods in implementation research in LMICs has previously been suggested as an important means of facilitating cross-culturally valid research in this setting (27). The methods described here represent a first step in achieving this goal.…”
Section: Discussionmentioning
confidence: 99%
“…Using an innovative methodology developed using the CFIR and extensive stakeholder engagement, five Implemention Plans for CST were produced for three countries. The systematic development of methods in implementation research in LMICs has previously been suggested as an important means of facilitating cross-culturally valid research in this setting (27). The methods described here represent a first step in achieving this goal.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the above, there is a case for urgent social and clinical need to validate interventions for PwD in developing regions. Indeed, non‐pharmacological treatment options are not offered routinely in developing countries 11 and little is known about their effectiveness in these regions 15 . There is limited data regarding CST efficacy in low‐ and middle‐income countries 16 and the current study may add valuable information for future development in this field.…”
Section: Introductionmentioning
confidence: 91%
“…18 Cultural adaptation enhances the appropriateness, uptake and chance for subsequent 'scale-up' of the intervention. 19 Thus, to adapt the original Montessori method therapy manual (with permission) to the context of a care home in Pakistan, we followed a modified cultural adaptation approach, based on a more complex framework of adaptations outlined by Barrera and Castro. 20 According to this framework, cultural adaptation should involve four phases, namely information gathering, preliminary adaptation design, preliminary adaptation testing and adaptation refinement.…”
Section: Stage 1: Cultural Adaptation Of the Interventionmentioning
confidence: 99%